A population of naive‐like CD4+ T cells stably polarized to the TH1 lineage. Issue 4 (12th February 2022) - Lo, Jonathan W.; de Mucha, Maria Vila; Henderson, Stephen; Roberts, Luke B.; Constable, Laura E.; Garrido‐Mesa, Natividad; Hertweck, Arnulf; Stolarczyk, Emilie; Houlder, Emma L.; Jackson, Ian; MacDonald, Andrew S.; Powell, Nick; et al.
Abstract: T‐bet is the lineage‐specifying transcription factor for CD4 + TH 1 cells. T‐bet has also been found in other CD4 + T cell subsets, including TH 17 cells and Treg, where it modulates their functional characteristics. However, we lack information on when and where T‐bet is expressed during T cell differentiation and how this impacts T cell differentiation and function. To address this, we traced the ontogeny of T‐bet‐expressing cells using a fluorescent fate‐mapping mouse line. We demonstrate that T‐bet is expressed in a subset of CD4 + T cells that have naïve cell surface markers and transcriptional profile and that this novel cell population is phenotypically and functionally distinct from previously described populations of naïve and memory CD4 + T cells. Naïve‐like T‐bet‐experienced cells are polarized to the TH 1 lineage, predisposed to produce IFN‐γ upon cell activation, and resist repolarization to other lineages in vitro and in vivo. These results demonstrate that lineage‐specifying factors can polarize T cells in the absence of canonical markers of T cell activation and that this has an impact on the subsequent T‐helper response.